Life in Recovery from Addiction in Canada: Examining Gender Pathways with a Focus on the Female Experience. Issue 4 (2nd October 2018) - McQuaid, Robyn J.; Dell, Colleen
ABSTRACT: The first Life in Recovery (LIR) from Addiction survey in Canada showed that individuals experience various pathways to recovery. The current study examines the recovery experiences among adult females with data from the 2016 Canadian LIR survey, with a focus on two well-established predictors of female substance use disorders, namely, family violence and mental health, for their impact on the recovery journey. Reasons for starting recovery varied by females and males, as a higher proportion of females (70.2%) reported their mental health as a factor for wanting to start recovery compared to males (64.7%). Moreover, females reported greater untreated mental health or emotional concerns during addiction compared to males, p = .003, as well as greater family violence during recovery, p = .02 and addiction, p < .001. In terms of informal supports, females are more likely to use technology as a recovery support, p < .05, are more likely to connect with a pet or other animal, p = .001, and are more likely to use art, poetry, writing, p = .007, and yoga, p < .001, as part of their recovery journey compared to males. These findings reveal females' unique addiction and recovery experiences and highlight the importance of considering gender implications, particularly for mental health and family violence, during the journey of addiction and recovery.